2008
DOI: 10.1021/jp8008404
|View full text |Cite
|
Sign up to set email alerts
|

Raman Studies of Monolayer Graphene: The Substrate Effect

Abstract: Graphene has attracted a lot of interest for fundamental studies as well as for potential applications. Till now, micromechanical cleavage (MC) of graphite has been used to produce high-quality graphene sheets on different substrates. Clear understanding of the substrate effect is important for the potential device fabrication of graphene. Here we report the results of the Raman studies of micromechanically cleaved monolayer graphene on standard SiO 2 (300 nm)/Si, single crystal quartz, Si, glass, polydimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
454
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 698 publications
(503 citation statements)
references
References 28 publications
(80 reference statements)
45
454
2
2
Order By: Relevance
“…The asymmetry between the conduction band () and the valence band (), which is especially pronounced in the vicinity of the point, which is attributed to the non-zero overlap parameter . However, the electronic band structure of graphene can be simply altered by applying electric field [6,5761] or providing substrates [62,63], and precisely engineered by introducing disorders into the hexagonal lattice [6468], which will be discussed in detail in later sections.…”
Section: The Structure Of Graphenementioning
confidence: 99%
“…The asymmetry between the conduction band () and the valence band (), which is especially pronounced in the vicinity of the point, which is attributed to the non-zero overlap parameter . However, the electronic band structure of graphene can be simply altered by applying electric field [6,5761] or providing substrates [62,63], and precisely engineered by introducing disorders into the hexagonal lattice [6468], which will be discussed in detail in later sections.…”
Section: The Structure Of Graphenementioning
confidence: 99%
“…Wang et al investigated the effect of substrates on the Raman spectrum of monolayer graphene. 30 The positions of the G and 2D bands were negligibly affected by substrates for the graphene prepared by mechanically cleavage of graphite, but were significantly blue-shifted for the epitaxially grown graphene on SiC. 30 They interpreted the blue shift in terms of the strain effect caused by the covalent bonding between SiC substrate and graphene.…”
Section: Resultsmentioning
confidence: 99%
“…30 The positions of the G and 2D bands were negligibly affected by substrates for the graphene prepared by mechanically cleavage of graphite, but were significantly blue-shifted for the epitaxially grown graphene on SiC. 30 They interpreted the blue shift in terms of the strain effect caused by the covalent bonding between SiC substrate and graphene. On the other hand, the red shift of the 2D band may be explained by a combination of effects caused by the strain and layer number.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional Raman topographical scans revealed that the film was >90% monolayer. After transfer onto a quartz substrate, the intensity of the D-band peak in the spectrum was not significantly changed, suggesting successful transfer to a more ideal substrate without significantly degrading graphene quality 12 .…”
Section: Graphene Characterizationmentioning
confidence: 99%